He2@C60: Thoughts of the concept of a molecule and of the concept of a bond in quantum chemistry. Issue 14 (15th July 2015) - Kryachko, Eugene S.; Nikolaienko, Tymofii Yu.
<x xml:space="preserve">Abstract</x> We present a broad palette of discussions of the concepts of a molecule and a chemical bond that always lay down behind all computational modeling in quantum chemistry and of the endohedral fullerene He2@C60 in particular. For this purpose, we offer the definition of quantum chemistry as composed of three ingredients. Each of them is illustrated by its particular concept, either that of a molecule or a bond. The third, computational ingredient is tackled to resolve the bonding manifold of He2@C60 and to demonstrate that van‐der‐Waals binding of HeHe is converted within He2@C60 into a stronger bond due to that C60 acts as an electronic buffer and [He2] moiety mimics a fractionally charged <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjrgxh6v7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />He2δ+</alternatives>. Experimental fingerprints of He2@C60 are computed. © 2015 Wiley Periodicals, Inc.